Candidati, eletti e temi del M5S in Toscana: una nuova offerta politica regionale - Luca Pighini (QOE-IJES, 2016)
The 2015 Italian local elections strengthen significantly the presence of the Five Star Movement (M5S) in Tuscany with the entry of new faces into more than 150 council members, including the city of Livorno. Both nationally and locally, the fall of 2014 brought about internal disputes within the political movement, and were followed by the resignation of many Tuscan councilmen and the leaving of many activists. Despite contrasting definitions, the M5S successfully manages this internal unrest and elaborates its political offer for the regional elections. The article wishes to reconstruct this political offer in light of the 2015 regional elections in Tuscany. It specifically analyses the following: the process of selection, the background of candidates, the main issues of the electoral campaign and their results. What are the territories where the M5S was rooted the most? What are the profiles of the elected? What are their political stances? The methodological frame is based on materials collected from the movement's website, media coverage, public initiatives and face-to-face interviews with M5S candidates (elected and not).